R E V I E W: Herbarium Celebense (CEB) and its role in supporting research on plant diversity of Sulawesi - RAMADHANIL RAMADHANIL; S. ROBERT GRADSTEIN (Society for Indonesian Biodiversity, 2004)
Sulawesi is the largest island in Wallacea region and a biogeographically unique area. The island is very rich in endemic species, worldwide known only known from Sulawesi. Nevertheless, scientific knowledge of the plants of Sulawesi is still limited and there is a lack of botanical exploration and publications. In 2000, Tadulako University of Palu with support of the German Research Foundation (DFG), the Universities of GÃ¶ttingen and Leiden and the Herbarium Bogoriense, hasconstructed a herbarium, the Herbarium Celebense. The herbarium has been registered in the International IndexHerbariorum (New York) with the abbreviation CEB. The Herbarium Celebense contains about 3000 plant specimens,especially from Central Sulawesi and mainly spermatophytes and pteridophytes. This article reviews the current knowedgeof plant diversity of the Sulawesi and Wallacea bioregion as a basis for the conservation of its rich flora.ïƒ£ 2004 Jurusan Biologi FMIPA UNS SurakartaKey words: central Sulawesi, Wallacea bioregion, flora, biogeography, plant diversity, endemic plants.